Hidden inequalities: The gendered labour of women on micro-tasking platforms - Paola Tubaro; Marion Coville; Clément Le Ludec; Antonio A. Casilli (Internet Policy Review, 2022)
Around the world, myriad workers perform micro-tasks on online platforms to train and calibrate artificial intelligence solutions. Despite its apparent openness to anyone with basic skills, this form of crowd-work fails to fill gender gaps, and may even exacerbate them. We demonstrate this result in three steps. First, inequalities in both the professional and domestic spheres turn micro-tasking into a 'third shift' that adds to already heavy schedules. Second, the human and social capital of male and female workers differ-leaving women with fewer career prospects within a tech-driven workforce. Third, female micro-work reproduces relegation of women to lower-level computing work observed in the history of science and technology.
Keywords: 300; gender; Digital platform labour; Gender bias; Inequality; Women; Social capital